ESTUDIO FITOQUÍMICO Y BIOQUÍMICO DE SEMILLAS PREHISPÁNICAS DE Nectandra sp. - Montoya Veraa, María (2019)
This article focuses on the study of a botanical specimen, that has been frcuently recovered in different archaeologic sites of the Peruvian coast north and central. Identified archaeobotanicly, it belongs to the Lauraceae family, gender Nectandra, kind yet unidentified, these seeds are own of forest areas wet  The origin and chronological location of the studied materials is Archaeologic Complex Huacas del Sol y la Luna located in the valley under of Moche, material associated with the late occupation Chimú (dated C14 1440 - 1665 a. C), In the present work have accomplished the analysis phytochemical and bioensays with extracts of these seeds, they were accomplished by specialists in pharmacology Currently its use continues being persistent, in coast and north saw (herbolarios, quacks), as well as between communities aguarunas of the north jungle. Its meant symbolic is framed in ritual aspects, as an element to offer in complex funeral ceremonies, of which have been able to glimpse recurrent contexts associated with possible child sacrifices - adolescent for the era Chimú. Being apparently that the pharmacological properties of these seeds were known and taken advantage from the pre-Hispanic era, such and as the references ethnohistorics already were outlining us.